Fabrication and Characterization of a Thermophone Based on Laser-Scribed Graphene Intercalated with Multiwalled Carbon Nanotubes - Moin Rabbani (MDPI AG, 2021)
The low sound pressure level and high operating voltages of thermophones have limited their applications in the past. However, in recent years, utilizing nanomaterials in thermophones has improved their efficiency and applicability. Nanomaterials, especially carbon nanotubes and graphene, have the advantage of low heat capacity per unit area (HCPUA) and high electrical and thermal conductivity. Therefore, they require a low electrical input power and generate a high sound pressure level (SPL) by efficiently transferring heat to the surrounding fluid. Laser-scribed graphene (LSG) can generate smooth spectra acoustic emissions over a wide range of frequencies by means of thermoacoustic (TA) emission. In this work, a thermophone based on LSG intercalated with multiwalled carbon nanotubes (MWCNTs) is proposed. The effects of varying input power, duty cycle percentage and measuring distance on the sound pressure level (SPL) of thermophones are studied to extract maximum efficiency. The achieved SPL of LSG, normalized to the input power, has increased by approximately 11 dB by intercalating it with MWCNTs, which shows that our proposed material can be a potential candidate for an efficient thermophone.